Aspectos nutricionais de genótipos de cafeeiro Conilon cultivados em altitude de transição sob manejos de água no solo - Salles, Rodrigo Amaro de (2020)
The nutritional characterization of conilon coffee genotypes is an important tool that can be applied in crop nutrition or even in a breeding program. However, soil water availability can severely affect nutrient absorption and accumulation over time. In